1997
DOI: 10.1109/10.554764
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic neuromuscular model for describing the pendulum test of spasticity

Abstract: Both dynamic and static thresholds, as well as the gain in the stretch reflex loop, affect the sensitivity of motoneurons to muscle stretch. How the variation in each parameter will influence the mechanical behavior of patients with spasticity is not well understood because of the difficulty in experimentally isolating individual parameters. A neuromuscular dynamic model, based on the pendulum test of spasticity, has been developed to study the specific contribution of individual parameter abnormalities in str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Our simulations suggest that non-vertical resting leg angle that increases with the severity of spasticity in individuals with CP is due to increased muscle tone. Most previously proposed models of the pendulum test were not able to account for the non-vertical resting angle whereas He et al described it using increased reflex muscle activity due to velocity feedback [ 5 ]. We also found that increased length feedback gains could result in a less vertical resting angle, but gain changes were not necessary when muscle tone was sufficiently high ( Fig 6 , baseline torque normalized to mass and length increases with spasticity severity).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our simulations suggest that non-vertical resting leg angle that increases with the severity of spasticity in individuals with CP is due to increased muscle tone. Most previously proposed models of the pendulum test were not able to account for the non-vertical resting angle whereas He et al described it using increased reflex muscle activity due to velocity feedback [ 5 ]. We also found that increased length feedback gains could result in a less vertical resting angle, but gain changes were not necessary when muscle tone was sufficiently high ( Fig 6 , baseline torque normalized to mass and length increases with spasticity severity).…”
Section: Discussionmentioning
confidence: 99%
“…Previous neuromechanical models have had difficulty in reproducing key changes in pendulum test kinematics in spastic individuals, particularly the decreased first swing excursion [ 4 , 5 , 6 , 7 ]. Previous studies have focused on modeling the effects of increased reflex activity as the underlying cause of abnormal pendulum test kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies of spasticity, few have used a portable system in their experiments. Some of the existing portable systems utilize a flexible electrogoniometer (based on strain gauge mechanism) [ 41 , 42 , 43 , 44 ], which is a simple method for measuring the joint angles. However, the resulting measurements would not be robust to the sensor placement; for instance, if the sensor is not perfectly aligned with the frame of motion.…”
Section: Objective Approachesmentioning
confidence: 99%
“…Most of the studies have used horizontal plane as their frame of reference [6, 16-18, 26, 29, 34, 42]. The second most popular frame of reference for angular movement is rest angle or the nal position of the knee in the pendulum test [27,33,35,36,43,50]. Some of the researchers have used the initial angle of the shank as their reference instead of horizontal plane [39,45,49].…”
Section: Relative Area Differencementioning
confidence: 99%
“…No researcher has used vertical plane as their reference in knee angle measurement. One example of such ambiguity is A0 which depending on the reference is de ned as "Final resting angle" [45] as well as "knee angle at the beginning of the test during maximal limb extension" [17,35]. Similarly, differences can be observed in the de nition of other spasticity measures such is de nition of RI in [6,18] and in [33,43].…”
Section: Relative Area Differencementioning
confidence: 99%